Legal Analysis of Criminal Liability of Directors and Commissioners in Corporate Crimes - Tri Sandi; Zefri Ansari; Peter Valentino Munthe; Sumarno Sumarno; Suci Ramadani (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2026)
ABSTRACT This study examines the role of directors and commissioners in corporate crimes from the perspective of criminal liability based on developments in national criminal law. The enactment of Law Number 1 of 2023 concerning the Criminal Code brought about important changes because corporations are expressly recognized as subjects of criminal offenses as regulated in Article 45. Articles 46 through 49 expand the scope of perpetrators, the criteria for corporate crimes, and the parties who can be held accountable, including managers, those who give orders, those who control, and beneficial owners. This study uses a normative legal research method with both a statutory and conceptual approach. The results indicate that directors hold a strategic position in corporate crimes because they carry out the functions of managing, making decisions, and controlling the company's operations. Meanwhile, commissioners have a supervisory and advisory function to directors, so they can be held accountable if there is negligence, approval, serious negligence, or factual control over criminal acts committed by corporations. From a criminal law perspective, the accountability of directors and commissioners cannot be based solely on formal positions, but must be proven through the relationship between authority, errors, actions, corporate profits, corporate policies, and failure to implement preventative measures and comply with the law. This research confirms that the theories of identification, vicarious liability, organizational culpability, and piercing the corporate veil can be used to understand the human involvement behind corporations. Therefore, corporate criminal liability must be balanced, namely by not allowing corporations to become a shield for crime, but also by not criminalizing directors and commissioners without a clear basis for culpability.